SEMANTIC CLASSIFICATION OF TOPONYMS OF SHOMANAY DISTRICT (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article discusses the emergence and change of toponyms based on certain laws related to people close to a person and changes in society. The research classifies the toponyms in the Shomanay district according to their naming motive and lexical-semantic properties. The toponyms in the district are primarily related to the Karakalpak tribes, their history, migration, and the ethnic structure of the area is reflected in the toponyms. The article also discusses the transformation of human names and swear words into geographical names, which is a widespread linguistic phenomenon, and how they occupy a significant place in the toponyms of the Shomanay district. Finally, the article talks about toponyms made from zoonyms and how they are based on appellative words that express the names of domestic animals, animals, and birds.